2016
DOI: 10.1007/s11523-016-0442-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fatty Acid Synthase Inhibition by Orlistat on Proliferation of Endometrial Cancer Cell Lines

Abstract: Orlistat inhibits cell growth in endometrial cancer cell lines through inhibition of fatty acid metabolism, induction of cell cycle G1 arrest, activation of AMPK and inhibition of the mTOR pathway. Given that patients with endometrial cancer have high rates of obesity, orlistat should be further investigated as a novel strategy for endometrial cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Consistent to previous reports, our current data also indicated that GDM significantly enhances the harmful lipid levels both in plasma and in liver. ACC was reported to provide the malonyl-CoA as a substrate for the biosynthesis of fatty acids [ 43 ]. Our data indicated that phosphorylations of ACC in GDM groups were significantly inhibited, while total ACC protein levels were increased, implying that the ACC activity was enhanced in GDM state.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent to previous reports, our current data also indicated that GDM significantly enhances the harmful lipid levels both in plasma and in liver. ACC was reported to provide the malonyl-CoA as a substrate for the biosynthesis of fatty acids [ 43 ]. Our data indicated that phosphorylations of ACC in GDM groups were significantly inhibited, while total ACC protein levels were increased, implying that the ACC activity was enhanced in GDM state.…”
Section: Discussionmentioning
confidence: 99%
“…ACC, as the rate limiting enzyme, plays a vital role in the synthesis of fatty acid, mainly phosphorylated by the upstream factor p-AMPK to inhibit fatty acid activation and promote fatty acid oxidation to achieve the reduction of the fatty acid synthesis [ 33 36 ]. By evaluating the alterations of placenta glucose and fatty acid metabolism related factors, we found that the mRNA and phosphorylation of ACC in GDMM group were significantly inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…It shows promising inhibitory effect on cell proliferation as well as tumor growth in prostate and breast cancer cells. 22 The finding that orlistat could reduce the uptake of 18 F-FPA by up to 42.7% in HCC cells indicated the important role of FASN in 18 F-FPA uptake. In accordance with the results of immunofluorescence and proteomic analyses, the expression of FASN was in the same order which may help explain the mechanism of 18 F-FPA uptake.…”
Section: Discussionmentioning
confidence: 94%